Tahfidz Al-Qur'an: A Study of Learning Management at Integrated Islamic Junior High School - Fransisko Chaniago; Siti Raudhatul Jannah; Fadlilah Fadlilah; Suci Fitriani; Sri Ramdayeni Sakunti; Shaudah Shaudah (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2024)
This study aims to analyze learning management of Al-Qur'an memorization (Tahfidz Al-Al-Qur'an) at An-Nahl Integrated Islamic Junior High School in Jambi. The approach employed in this study was descriptive approach, utilizing qualitative methods with data collection instruments such as observation, interviews, and documentation. The data used in this research undergoes data reduction, data display, and conclusion drawing. The results of this study indicate that the learning management of Al-Qur'an memorization at An-Nahl Integrated Islamic Junior High School in Jambi has been effectively implemented. This Al-Qur'an memorization learning is facilitated through the collaboration among the school principal, the Chairman of the foundation, the Curriculum Vice Principal, the Student Affairs Vice Principal, and the Tahfidz teachers who are responsible for optimizing the Al-Qur'an learning process and providing greater understanding of the importance of memorizing the Al-Qur'an for the students. This achievement is closely related to the adjustment of planning, organization, implementation, and evaluation processes of Al-Qur'an memorization learning at An-Nahl Integrated Islamic Junior High School in Jambi.